JUVENILE DELIQUENCY AMONG CHILDREN PRISONERS - Nurianto Dodid; Retno Ristiasih Utami; Anna Dian Savitri (Proyeksi: Jurnal Psikologi, 2012)
This research attempt to identify the juvenile delinquency among children prisoner in Kutoarjo ChildrenPrison and also determine the factors cause of juvenile delinquency, the reasons why they dodelinquent and the effects of juvenile delinquency. The subjects were three boy and two girl prisoners.Interview, observation and documents analysis were used to collect data in this qualitative research.The data were analyzed by data reduction, coding and verification.Results indicate that the factors cause of juvenile delinquency among children prisoner are external andinternal factors. The external factors is family structure or disharmonic communication between parentsand children. The internal factors are sexuality drive and their hedonistic manner. The effects of juveniledelinquency increase number children or teenagers that being against the law and sexual harassment tothe girls inmate.